2008
DOI: 10.1287/mnsc.1080.0940
|View full text |Cite
|
Sign up to set email alerts
|

Capacity Investment Under Postponement Strategies, Market Competition, and Demand Uncertainty

Abstract: We consider duopoly models where firms make decisions on capacity, production, and price under demand uncertainty. Capacity and price decisions are made, respectively, ex ante and ex post demand realizations. The interplay between the timings of demand realization and production decision endows firms with different capabilities. Flexible firms can postpone production decisions until the actual demand curve is observed, but inflexible firms cannot. Under general demand structures and cost functions, we characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(69 citation statements)
references
References 21 publications
3
66
0
Order By: Relevance
“…In many settings, flexibility is a tool to cope with variability in the external environment, and so investing in flexibility is sensible provided that the variability in the external environment is sufficiently high (Tombak and DeMeyer 1988, Mills 1984, Anupindi and Jiang 2008, Chod and Rudi 2005, Goyal and Netessine 2011. Proposition 3 identifies circumstances under which precisely the opposite is true regarding flexibility in input efficiency versus capacity efficiency.…”
Section: Flexibility In Input Efficiency Vs Capacity Efficiencymentioning
confidence: 99%
“…In many settings, flexibility is a tool to cope with variability in the external environment, and so investing in flexibility is sensible provided that the variability in the external environment is sufficiently high (Tombak and DeMeyer 1988, Mills 1984, Anupindi and Jiang 2008, Chod and Rudi 2005, Goyal and Netessine 2011. Proposition 3 identifies circumstances under which precisely the opposite is true regarding flexibility in input efficiency versus capacity efficiency.…”
Section: Flexibility In Input Efficiency Vs Capacity Efficiencymentioning
confidence: 99%
“…Within a capacity constrained environment even allowing Bertrand type price competition can lead to a Cournot competition at the point of capacity investment (Kreps and Scheinkman, 1983). In the same way Anupindi and Jiang (2008) have suggested that price competition can also be modeled in this way if firms have some flexibility to exercise control on quantity through production or delivery. Due to its analytical simplicity, the choice of linear demand is conventional and this is often a good approximation to more general demand functions (see Shapiro, 1986).…”
Section: Model Descriptionmentioning
confidence: 99%
“…In this case the degree to which holdback is employed is a function of changing market conditions which are unknown at the outset. However, in this paper we concentrate on the simplest case in which a production quantity is set only once (following the operations literature including Anupindi and Jiang (2008)) and uncertainty in market conditions is sufficiently small that it can be ignored (following the economics literature including Dixit (1980)). …”
Section: Introductionmentioning
confidence: 99%
“…Choosing unified production process enables a firm to manufacture the final product with lower costs and also can be interpreted as a strategic commitment device whereby a firm commits to bring a certain quantity to market (Anupindi, Jiang 2008). On the other hand, choosing modular production process implies that a firm invests on a more expensive technology which empowers it to manufacture the final product with higher costs by producing a general component -which can be used in other productsassembled sequentially with a specific component which is specialized for certain product based on the demand information of the market.…”
Section: The Modelmentioning
confidence: 99%